Tributyltin and Zebrafish: Swimming in Dangerous Water - Berto-Júnior, Clemilson; de Carvalho, Denise Pires; Soares, Paula; Miranda-Alves, Leandro (Frontiers in Endocrinology, 2018)
Zebrafish has been established as a reliable biological model with important insertion in academy (morphologic, biochemical, and pathophysiological studies) and pharmaceutical industry (toxicology and drug development) due to its molecular complexity and similar systems biology that recapitulate those from other organisms. Considering the toxicological aspects, many efforts using zebrafish models are being done in order to elucidate the effects of endocrine disruptors, and some of them are focused on tributyltin (TBT) and its mechanism of action. TBT is an antifouling agent applied in ship’s hull that is constantly released into the water and absorbed by marine organisms, leading to bioaccumulation and biomagnification effects. Thus, several findings of malformations and changes in the normal biochemical and physiologic aspects of these marine animals have been related to TBT contamination. In the present review, we have compiled the most significant studies related to TBT effects in zebrafish, also taking into consideration the effects found in other study models.